1985
DOI: 10.1073/pnas.82.22.7782
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of electrically excitable cells in cultured olfactory epithelium.

Abstract: A primary system has been developed in which it is possible to study the production of electrically excitable neuron-like cells from a precursor population of olfactory epithelial cells. Rat nasal epithelium was dissociated and placed in culture. The initial surviving cells are flat and ciliated and contain glial fibrillary acidic protein (GFAP). After 3-5 days electrically excitable cells appear that contain neuronspecific enolase but not GFAP. These round cells originate by means of the differentiation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Several previous studies support the view that the olfactory placode can generate a variety of neurons and sheath cells (Doucette 1989;Farbman and Squinto Mendoza et al 1982;Murakami et al 1991Murakami et al , 1992Schubert et al 1985;Schwanzel-Fukuda and Pfaff 1989;Wray et al 1989a, b). It is possible that cells of placodal origin incorporated into the brain of the host under our experimental conditions are induced to differentiate and to express a different phenotype spectrum from the one typically expressed by cells that mature in their normal habitat.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several previous studies support the view that the olfactory placode can generate a variety of neurons and sheath cells (Doucette 1989;Farbman and Squinto Mendoza et al 1982;Murakami et al 1991Murakami et al , 1992Schubert et al 1985;Schwanzel-Fukuda and Pfaff 1989;Wray et al 1989a, b). It is possible that cells of placodal origin incorporated into the brain of the host under our experimental conditions are induced to differentiate and to express a different phenotype spectrum from the one typically expressed by cells that mature in their normal habitat.…”
Section: Discussionmentioning
confidence: 67%
“…It has been suggested that some cells migrating along the fascicles of the olfactory nerves could be incorporated into the olfactory bulb as a special type of glial cell (Doucette 1989). According to recent in vitro studies, cells derived from the olfactory epithelium could act as pluripotent precursors for both glial and neuronal cells (Schubert et al 1985). Moreover, recent transplantation studies have demonstrated that cells isolated from the embryonic and postnatal epithelia of the rat, when transplanted into the CNS of embryonic rats at E15, can change their fate and become either glia or neurons according to their new final location (Magrassi and Graziadei 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies (3)(4)(5) clearly have demonstrated an odorant-dependent increase of adenylyl cyclase activity in preparations of cilia from frog or rat OE. It seemed that the SNIF cell strains, derived from the OE, might be capable of responding to odorant stimuli by production of a second messenger such as cAMP.…”
Section: Resultsmentioning
confidence: 99%
“…Past attempts to grow these cells in culture (3,10,11) did not yield strains that were differentiated sufficiently to suggest their use in the study of olfaction in vitro. We report here that two of three cloned cell strains, although they appear to be incompletely differentiated neurons in culture, have nevertheless responded sensitively and selectively to test odorants by accumulating cAMP.…”
mentioning
confidence: 99%
See 1 more Smart Citation